Guanidinoacetic Acid as a Nutritional Adjuvant to Multiple Sclerosis Therapy - Ostojic, Sergej M. (Frontiers in Human Neuroscience, 2022)
Tackling impaired bioenergetics in multiple sclerosis (MS) has been recently recognized as an innovative approach with therapeutic potential. Guanidinoacetic acid (GAA) is an experimental nutrient that plays a significant role in high-energy phosphate metabolism. The preliminary trials suggest beneficial effects of supplemental GAA in MS, with GAA augments biomarkers of brain energy metabolism and improves patient-reported features of the disease. GAA can also impact other metabolic footprints of MS, including demyelination, oxidative stress, and GABA-glutamate imbalance. In this mini-review article, we summarize studies evaluating GAA effectiveness in MS, explore mechanisms of GAA action, and discuss the challenges of using dietary GAA as an element of MS therapy.